A STUDY OF GRAMMATICAL AND MECHANICAL ERRORS IN STUDENTS' RECOUNT TEXTS ON THE SECOND YEAR STUDENTS OF SMPIT SABBIHISMA PADANG - Christina, Dian (RC-INSTITUT, 2017)
The aim of this research is to identify types and level of grammatical and punctuation errors made by the students in writing recount. This is the descriptive quantitative research in content text analysis. The population of this research was the second year students of Junior High School which consists 24 students. In analyze the data, the researcher described about the types of Grammatical and Mechanical errors. Grammatical Errors were grouped into four classes. First, there are three types of language use errors found in using linking verb. They were omission (20%), addition (27%) and selection (14%). Second, in using action verb. They are omission (35%), addition (48%) and selection (35%). Third, there is one type of language use errors found in using pronoun that is omission (08%). Last, there is one type in using possessive that is selection (17%). Meanwhile, in the mechanics they were grouped into four classes. First, there are three types of mechanics errors found in using period. They are omission (53%), addition (23%) and selection (5%). Second, there are three types in using comma. They are omission (9%), addition (11%) and selection(38%).